Crowned dens syndrome: A case series of 72 patients at eight teaching hospitals in Japan - Hiroki Isono; Haruka Kuno; Takunori Hozumi; Ken Emoto; Sho Nishiguchi; Masahiro Sakai; Madoka Ito; Koichi Kitamura; Kazuhito Hirose; Eiji Hiraoka; Naoto Ishimaru; Hiroyuki Kobayashi; et al. (Journal of General and Family Medicine)
Abstract Background Crowned dens syndrome (CDS) is characterized by calcification around the odontoid process, accompanied by neck pain. Although CDS is supposedly rare, we regularly diagnose and manage this condition, indicating a perception gap between previous studies and our experience. The purpose of this study was to determine the annual incidence of CDS, time to diagnosis in CDS, as well as the features of CDS. Methods The study design was a retrospective case series study conducted at eight teaching hospitals in Japan. We identified CDS cases from April 2013–March 2015. CDS was diagnosed when patients had acute onset of neck pain and CT showed calcification around the dens and when other diagnoses were unlikely. Results Seventy‐two CDS cases were identified. Mean annual incidence was 4.6 ± 2.3 cases at each hospital. Among those with available data, 57 of 64 had limited rotation (89.1%). The diagnosis of CDS was made in general internal medicine or the emergency medicine department in 61 cases (84.7%). A total of 62 cases (86.1%) were diagnosed within 1 day of presentation, and the median time from initial presentation at the hospital to diagnosis was 0.0 days (25th–75th percentiles, 0.0–1.0). For treatment, NSAIDs were used in 56cases (77.8%) and acetaminophen in 20 cases (27.8%). Conclusion CDS might be more common than has been reported to date. Time to diagnosis of CDS was within 1 day of visiting a teaching hospital. Cervical motion restriction is common in CDS and may be useful in establishing the diagnosis.